Chronic brucellosis with sacroiliitis: A case report - Bibek Shrestha; Pradeep Shrestha; Sudip Bastakoti; Prahlad Gupta; Shiva Ram Ale Magar (Clinical Case Reports)
Key Clinical Message Brucellosis, especially with osteoarticular involvement, is uncommon and difficult to diagnose, but it should be considered in a case presenting with prolonged fever, joint pain, and back pain. The diagnosis requires a combination of history, serological examinations, and radiographic studies. When the condition is detected and treated early, the prognosis is good. Abstract Brucella exploits host immune defenses to establish the chronic infection brucellosis, an endemic zoonotic disease. While human brucellosis affects multiple organs, osteo articular involvement is rare. We report the case of a 41‐year‐old woman with a history of goat farming who presented with fewer associated with low back pain and multiple joint pain for 4 months. Brucellosis was documented by positive serological tests (ELISA). Radiological findings suggested of right sacroiliitis and fracture line on the right sacral ala though had no history of trauma. Treatment consisted of NSAIDs and multiple antibiotic therapy. At follow‐up, her low back pain, joint pain, and fever had subsided. After 4 weeks of follow‐up, her symptoms were completely relieved with no recurrence. Brucellosis with atypical localization should be considered with a high index of suspicion based on detailed history and physical examination to ensure timely diagnosis and treatment.